The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/2150135116682465
|View full text |Cite
|
Sign up to set email alerts
|

Sinus of Valsalva Aneurysm in a Patient With Mosaic Trisomy 13: Case Report and Brief Review of the Literature

Abstract: This report describes a unique case involving an obese 16-year-old boy with a mosaic form of trisomy 13 and no previous cardiac history who presented with a new murmur, hypertension, pleural effusions, and congestive heart failure in the context of sore throat and fever. Evaluation revealed a diagnosis of ruptured noncoronary sinus of Valsalva (SOV) aneurysm. The diagnosis and surgical management of a ruptured noncoronary SOV aneurysm in a pediatric patient are briefly outlined. An SOV aneurysm is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Most of the patients with trisomy 13 die before completing the first year of life and only 5%-10% can survive beyond the first year. In contrast to complete trisomy 13, patients with mosaic trisomy 13 present with fewer and milder anomalies and may survive to late childhood and adulthood [7]. The diagnosis in this case report was made through chromosomal analysis of cultured peripheral blood sample, and it revealed a mosaic result.…”
Section: Discussionmentioning
confidence: 74%
“…Most of the patients with trisomy 13 die before completing the first year of life and only 5%-10% can survive beyond the first year. In contrast to complete trisomy 13, patients with mosaic trisomy 13 present with fewer and milder anomalies and may survive to late childhood and adulthood [7]. The diagnosis in this case report was made through chromosomal analysis of cultured peripheral blood sample, and it revealed a mosaic result.…”
Section: Discussionmentioning
confidence: 74%
“…Mosaicism was also present in the first reported case of aortic dilatation in trisomy 13 mosaicism. Ghawi et al 7 presented a 16-year-old male patient with trisomy 13 mosaicism with no previous cardiac history who had a new murmur, hypertension, and congestive heart failure. The management included initial stabilization on the night of admission with a diuretic and an antihypertensive agent, along with surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The management included initial stabilization on the night of admission with a diuretic and an antihypertensive agent, along with surgical intervention. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Ghawi et al reported a patient in adolescence with trisomy 13 and SVA rupture, in whom no cardiac anomalies were found in the neonatal period. SVA is associated with other CHD,16 18 most commonly VSD (44.2%) and aortic regurgitation (43.3%) 16 18 19. Detailed echocardiography is an accurate method for diagnosing SVA 16 20 21.…”
Section: Discussionmentioning
confidence: 99%